Hi everyone, we are needing help on a multi-step equation.
In this problem:
we are not understanding how they are getting the -4x on the left side.
What did you obtain when you added the -1x and the -3x? Kindly please include all of your steps, so that error-correction may be attempted. Thank you.Hi everyone, we are needing help on [solving] a multi-step equation.
In this [worked solution]:
we are not understanding how they are getting the -4x on the left side.Code: Select all
-x - 2 = 3x + 5 -1x - 2 = 3x + 5 -3x -3x ---------------- -4x - 2 = 0x + 5 <=== -4x - 2 = 5 -4x - 2 = 5 + 2 = +2 ------------ -4x + 0 = 7 -4x = 7 -4x = 7 --- --- -4 -4 x = 7/(-4) = -7/4
How many x's are in "x"? Is this not one "x"? While the "1" is "understood" and not (usually) included, "1x" is equivalent to "x".Hi, thank you for your response. We are not understanding how in your example of the problem, there is a -1x. In the original problem that I posted, there is no -1x. Please explain how you got this number. Thank you.